2022
DOI: 10.3390/ani12111337
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Metabolic Profile Changes in Heat-Stressed Broilers

Abstract: Heat stress (HS) is devastating to poultry production sustainability worldwide. In addition to its adverse effects on growth, welfare, meat quality, and mortality, HS alters the gut integrity, leading to dysbiosis and leaky gut syndrome; however, the underlying mechanisms are not fully defined. Here, we used a high-throughput mass spectrometric metabolomics approach to probe the metabolite profile in the duodenum of modern broilers exposed to acute (AHS, 2 h) or chronic cyclic (CHS, 8 h/day for 2 weeks) HS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 170 publications
0
5
0
Order By: Relevance
“…As per literature reports, the balance of the intestinal microbiota plays a crucial role in the pathogenic mechanisms in animals [25,[29][30][31]. The intestinal microbiota is closely associated with intestinal inflammation, and the metabolites of the microbiota can influence the levels of inflammatory factors, thereby affecting the interaction between the host and microorganisms.…”
Section: Discussionmentioning
confidence: 88%
“…As per literature reports, the balance of the intestinal microbiota plays a crucial role in the pathogenic mechanisms in animals [25,[29][30][31]. The intestinal microbiota is closely associated with intestinal inflammation, and the metabolites of the microbiota can influence the levels of inflammatory factors, thereby affecting the interaction between the host and microorganisms.…”
Section: Discussionmentioning
confidence: 88%
“…Samples were sent to the Biological and Small Molecule Mass Spectrometry Core (RRID: SCR_021368). As previously described [ 16 , 17 ], and in brief, metabolites were extracted using 1.5 mL of extraction solvent (40:40:20 HPLC grade methanol: acetonitrile: 0.1 M final concentration of water with formic acid), prechilled at 4 °C, and incubated at −20 °C for 20 min. The samples were centrifuged at 13,300× g for 5 min at 4 °C before the supernatants were collected.…”
Section: Methodsmentioning
confidence: 99%
“…The metabolites’ fold change and p -value were entered into the IPA, along with their identifications, from the Human Metabolome Database, denoted as HMDB [ 24 ]; the Kyoto Encyclopedia of Genes and Genomes, denoted as KEGG [ 25 ]; and the Chemical Entities of Biological Interest, denoted as ChEBI [ 26 ]. IPA analysis was completed as previously described [ 17 ]. Briefly, the top canonical pathways and functional annotations were deduced for differentially expressed metabolites via IPA analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cecum is the broiler gastrointestinal tract’s most diverse area of microbes and various microbes are crucial in improving growth performance and maintaining physical health ( Luo et al, 2021 ). Previous studies mainly explored the effects of heat stress on broiler intestines from a single omics perspective, including transcriptome, metabolomics, and microbiome ( Dridi et al, 2022 ; Kim et al, 2022 ; Zhang Y. et al, 2023 ; Zhang F. et al, 2023 ; Zhang X. et al, 2023 ). However, very few studies have comprehensively revealed the heat-stress impact on broilers’ guts.…”
Section: Introductionmentioning
confidence: 99%